Molecular Modelling Analysis of the Metabolism of Oseltamivir - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
Molecular modelling analyses based on molecular mechanics, semi-empirical (PM3) and DFT (at B3LYP/6-31G* level) calculations show that oseltamivir (OSE) and its metabolite oseltamivir carboxylate (OSA) have large LUMO-HOMO energy differences of 4.7 to 4.6 eV, respectively indicating that the compounds would be moderate inert kinetically. The molecular surfaces of the compounds are found to abound in neutral green and electron-rich red and yellow regions so that they may be subjected to lyophilic and electrophilic attacks. The molecular surfaces of OSE and OSA are also found to possess a small amount of electron-deficient blue regions so that the compounds may be subject to nucleophilic attacks. Nucleophilic attacks may be due to glutathione and nucleobases in DNA as a result of which depletion of glutathione and oxidation of nucleobases in DNA may occur. The former would induce oxidative stress and hence cellular toxicity whereas the latter would cause DNA damage. However, because of kinetic inertness of the molecules and paucity of electron-deficient regions, the rates of such adverse reactions are expected to be low.